2017
DOI: 10.1242/jcs.194779
|View full text |Cite
|
Sign up to set email alerts
|

Vinculin promotes nuclear localization of TAZ to inhibit ECM stiffness-dependent differentiation into adipocytes

Abstract: Extracellular matrix (ECM) stiffness regulates the lineage commitment of mesenchymal stem cells (MSCs). Although cells sense ECM stiffness through focal adhesions, how cells sense ECM stiffness and regulate ECM stiffness-dependent differentiation remains largely unclear. In this study, we show that the cytoskeletal focal adhesion protein vinculin plays a critical role in the ECM stiffness-dependent adipocyte differentiation of MSCs. ST2 mouse MSCs differentiate into adipocytes and osteoblasts in an ECM stiffne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 53 publications
6
69
0
Order By: Relevance
“…Variations in the amount of tension have been observed within the vinculin molecule at FAs [23]. In addition, vinculin is necessary for ECM stiffness-directed myoblast or adipocyte differentiation [24, 25]. In a previous study, we also showed that a stiff ECM promotes interactions between the vinculin linker region and vinexin α, resulting in the vinculin localization to lipid rafts [26] and the vinculin activation [27], thus stable localization of vinculin at FAs and vinculin resistance to CSB (cytoskeleton stabilization buffer).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in the amount of tension have been observed within the vinculin molecule at FAs [23]. In addition, vinculin is necessary for ECM stiffness-directed myoblast or adipocyte differentiation [24, 25]. In a previous study, we also showed that a stiff ECM promotes interactions between the vinculin linker region and vinexin α, resulting in the vinculin localization to lipid rafts [26] and the vinculin activation [27], thus stable localization of vinculin at FAs and vinculin resistance to CSB (cytoskeleton stabilization buffer).…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear localization of YAP/TAZ is promoted on rigid ECM in mesenchymal stem cells in a manner dependent on vinexin and vinculin expression (Kuroda et al, 2018(Kuroda et al, , 2017. To explore the role of H2 helix in the nuclear localization of YAP/TAZ, vinexin-KO MEFs re-expressing vinexin α WT or H2Q3 cultured on soft or rigid substrates were immunostained with anti-YAP/TAZ antibody (Fig.…”
Section: The Vinexin α H2 Helix Is Involved In Stiffness-dependent Rementioning
confidence: 99%
“…Vinexin α (an isoform encoded by the SORBS3 gene), another FA scaffold protein, cooperates with vinculin to work as a mechanosensor of ECM stiffness Kuroda et al, 2017;Yamashita et al, 2014). On rigid ECM, vinexin α interacts with vinculin in an actomyosin contractility-dependent manner and induces the conformational change in vinculin to an open form, promoting cell migration and the nuclear localization of the transcriptional co-activators, Yes-associated protein (YAP, also known as YAP1) and transcriptional coactivator with a PDZbinding motif (TAZ, also known as WWTR1) (hereafter YAP/ TAZ).…”
Section: Introductionmentioning
confidence: 99%
“…MSCs can be isolated from various tissues such as bone marrow, adipose tissue, and the umbilical cord . It has been observed that bone marrow‐derived MSCs can be differentiated into osteoblasts, adipocytes, and chondrocytes in vitro under chemical and physical stimuli …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] It has been observed that bone marrow-derived MSCs can be differentiated into osteoblasts, adipocytes, and chondrocytes in vitro under chemical and physical stimuli. [8][9][10][11][12] Studies have shown that substrates with microstructured or nanostructured surfaces could strongly influence the fate of MSCs. [13][14][15] Dalby and his colleagues reported that substrates with deliberately disordered pits in a square arrangement (±50-nm offset) induced MSCs to differentiate into osteoblasts, 16 while nanotopography with pits arranged in absolute square lattice symmetry retained stem-cell phenotype and maintained stem-cell growth of MSCs over 8 weeks.…”
Section: Introductionmentioning
confidence: 99%